PENGHAPUSAN KEBIJAKAN SUBSIDI EKSPOR OLEH WORLD TRADE ORGANIZATION (WTO) DAN DAMPAKNYA TERHADAP EKSPOR PRODUK PERTANIAN INDONESIA - ", Poniman; Yelta, Den (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The Government of Indonesia has ratified the Agreement on the Establishment of the World Trade Organization (WTO) through Law No. 7 of 1994. By ratifying it, Indonesia has an obligation to observe and comply with all the rules in the WTO, including agreements on agriculture (Agreement on Agriculture / AoA). In the AoA-WTO, there are three main pillars, namely 1. Market access, 2. Domestic Support, and 3. Export Subsidies.Export subsidies are government assistance contributed financially to domestic producers or exporters. The export of a commodity / product can be encouraged by the subsidy, because the price will be cheap and increase the competitiveness.Developing countries with low GDP are unable to provide export subsidies to their exporters, the price of goods is high. This causes the price gap between developed countries and developing countries. At the WTO conference in Nairobi the member states agreed to abolish export subsidies. This study aims to analyze the impact of the policy on abolishing export subsidies by the WTO.Keywords: World Trade Organization, Export Subsidies, Agreement on Agriculture